2011
DOI: 10.1186/1748-717x-6-142
|View full text |Cite
|
Sign up to set email alerts
|

Total error shift patterns for daily CT on rails image-guided radiotherapy to the prostate bed

Abstract: BackgroundTo evaluate the daily total error shift patterns on post-prostatectomy patients undergoing image guided radiotherapy (IGRT) with a diagnostic quality computer tomography (CT) on rails system.MethodsA total of 17 consecutive post-prostatectomy patients receiving adjuvant or salvage IMRT using CT-on-rails IGRT were analyzed. The prostate bed's daily total error shifts were evaluated for a total of 661 CT scans.ResultsIn the right-left, cranial-caudal, and posterior-anterior directions, 11.5%, 9.2%, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 15 publications
(26 reference statements)
1
9
0
Order By: Relevance
“…The mean movement calculated in this study is similar to that shown in previous studies . Table shows the mean magnitude and standard deviations of the prostate bed motion calculated by other groups who have also used CBCT imaging .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The mean movement calculated in this study is similar to that shown in previous studies . Table shows the mean magnitude and standard deviations of the prostate bed motion calculated by other groups who have also used CBCT imaging .…”
Section: Discussionsupporting
confidence: 86%
“…Variability was seen between the bony anatomy match and the surgical clip matches in all planes for both the superior and inferior clips, with the least difference in the L/R plane. Other groups have also found that movement is least in the lateral plane, and this was also seen to be the case in the definitive prostate setting . More movement was seen in all planes in the upper prostate bed than in the lower prostate bed.…”
Section: Discussionmentioning
confidence: 59%
“…Prostate bed motion (PBM) has been examined thoroughly by ultrasound-based technologies [10,11], by CBCT in combination of rectal wall or surgical clips localization [6,[12][13][14], by electronic portal imaging device (EPID) and gold seed fiducials localization [4], and by orthogonal kV images together with radiofrequency beacons or surgical clips localization [5,15]. In this study we investigate the prostate bed localization difference between soft tissue registration and gold seed fiducial localization.…”
mentioning
confidence: 99%
“…Previous authors have reported that the PB moves independently of bony anatomy, [15][16][17][18][19] and in a number of these studies CBCT scans were used to assess this movement. 10,20,21 This has implications for daily image guidance techniques applied during radiotherapy treatment in post-prostatectomy patients.…”
Section: Discussionmentioning
confidence: 99%